THE ROLE OF SUSTAINABLE HUMAN RESOURCES MANAGEMENT (SHRM) IN ENHANCING WORKPLACE DIPLOMACY ACCORDING TO THE SUSTAINABLE HOLISTIC MODEL-AN ANALYTICAL STUDY OF A SAMPLE OF WORKERS AT TIKRIT TEACHING HOSPITAL/SALAH AL-DIN GOVERNORATE - Assistant Professor Dr. Roy Ahmed Ibrahim; Assistant Teacher Mohammed Hammed Nayef; Teacher: Talha Kuan Salem (Scholars Digest Publishing, 2024)
The current research contributes to knowing the role of sustainable human resources management as an independent variable in promoting diplomacy in the workplace as a dependent variable according to the sustainable holistic model. One of the most important problems addressed is the extent of interest in sustainable human resources management in promoting workplace diplomacy according to the sustainable holistic model. Accordingly, a group was launched. Among the priority and secondary hypotheses in order to develop solutions to clarify the relationships between the research variables, and for this purpose, the questionnaire was adopted and selected in order to investigate and collect the necessary data to obtain the most accurate results, and thus it was adopted in order to monitor and choose the most important facility in life, which is the field of health in the Salah Health Department. Al-Din / Tikrit Teaching Hospital, where the research sample consisted of (89) employees. The data was analyzed using statistical software (Amos v.26). One of the most important conclusions reached by the research is the presence of a strong moral correlation and a statistically significant moral effect between the role of sustainable human resources management as an independent variable in promoting diplomacy in the workplace as a dependent variable according to the sustainable holistic model. The research came out with a set of recommendations, the most important of which is providing comprehensive support for the role of human resources. Sustainable efforts to enhance diplomacy in the workplace.
Keywords: sustainable human resources management, workplace diplomacy, holistic model.